2003
DOI: 10.2337/diacare.26.5.1439
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Is a Marker for Nephropathy and Peripheral Vascular Disease in Type 1 Diabetes

Abstract: -We examined whether plasma fibrinogen levels and the ␤-fibrinogen gene G Ϫ455 3 A polymorphism were related to microvascular or macrovascular disease in patients (n ϭ 909) with type 1 diabetes enrolled in the Diabetes Control and Complications Trial/ Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC). Univariate regression showed that fibrinogen levels were correlated with BMI (r ϭ 0.15; P Ͻ 0.0001), HbA 1c (r ϭ 0.11; P ϭ 0.0014), total cholesterol (r ϭ 0.17; P Ͻ 0.0001), and LDL cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 57 publications
0
47
0
1
Order By: Relevance
“…It has been suggested that the hyperglycaemia-induced formation of reactive oxygen species in mitochondria and the generation of AGE might be the link between endothelial cell damage and damage to glomerular cells, leading to albuminuria [30]. Fibrinogen has been found to predict progression of nephropathy [8][9][10], probably as a marker of renal vascular damage; however, its role in diabetic subjects could be even more complex than that of an indicator of atherothrombotic disease. Indeed, emerging evidence suggests that chronic inflammation may represent a component of the metabolic syndrome, as it has been associated with insulin resistance and cardiovascular risk factors in diabetic subjects [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the hyperglycaemia-induced formation of reactive oxygen species in mitochondria and the generation of AGE might be the link between endothelial cell damage and damage to glomerular cells, leading to albuminuria [30]. Fibrinogen has been found to predict progression of nephropathy [8][9][10], probably as a marker of renal vascular damage; however, its role in diabetic subjects could be even more complex than that of an indicator of atherothrombotic disease. Indeed, emerging evidence suggests that chronic inflammation may represent a component of the metabolic syndrome, as it has been associated with insulin resistance and cardiovascular risk factors in diabetic subjects [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cross-sectional studies have provided evidence that fibrinogen levels are independently associated with AER in both type 1 and type 2 diabetic subjects [8][9][10]; however, the pathophysiological relationship between these two factors and the clinical relevance of their combined effect on cardiovascular risk remain unknown. Recent prospective data from the Casale Monferrato Study have provided evidence that hyperfibrin-ogenaemia independently predicts progression to overt diabetic nephropathy in type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…In type 2 diabetes, fibrinogen levels have been demonstrated to predict the progression to overt nephropathy (10). Hyperfibrinogenemia, an indicator of inflammation, is also associated with the presence of endothelial dysfunction, insulin resistance, hypercoagulability, and increased blood viscosity and is a marker of unstable atherosclerotic lesions (11)(12)(13)(14)(15). The aim of the present study was to explore the relationships between low-grade inflammation markers, glomerular structure, and renal function in patients with type 2 diabetes.…”
mentioning
confidence: 96%
“…Also fibrinogen has been reported to be associated with both cardiovascular risk and nephropathy in type 1 and type 2 diabetes (10,11). The Diabetes Control and Complications Trial/Epidemiology of Diabetes Intervention and Complications (DCCT/EDIC) study group reported that fibrinogen is associated with AER, especially in men, but not with retinopathy and that a fibrinogen gene polymorphism is associated with peripheral vascular disease (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation